2019
DOI: 10.1021/acs.macromol.9b01623
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Copolymerization: Access to Aziridine Copolymers with Adjustable Gradient Strengths

Abstract: Competitive copolymerization gives access to gradient copolymers with simple one-step and one-pot strategies. Due to the living nature of the sulfonyl-aziridine polymerization, gradient copolymers can be obtained with low dispersities and adjustable molar masses. The combination of different sulfonyl activating groups allowed to fine-tune the reactivity difference of the comonomers and thus an exact adjustment of the gradient strength. Sulfonyl-activated aziridines are to date the only monomer class providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 68 publications
0
34
0
1
Order By: Relevance
“…The particular reactivity ratio of comonomers is the essential factor in regulating the sequence structure of monomer units during chain growth polymerization. For general polymerization systems ( r 1 × r 2 > 0), sequence regulation of monomer units cannot be realized, and only block or statistical (random and gradient) sequence distributions can be prepared. , Recently, Kamigaito et al proposed a strategy to obtain sequence-defined vinyl polymers containing two double bonds in the main chain via ROMP of template ring monomers, and the polymer subsequently treated by hydrogenation resulted in methylene/styrene/acrylate/styrene/ethylene (i.e., SASEM) as the repeating units in the hydrogenation product . ROMP of 4-phenylcyclopentene (4PCP) has also been investigated, and quantitative homogeneous hydrogenation of P4PCP results in a precision E/S copolymer with a C5 skeleton (i.e., SEM) .…”
Section: Resultsmentioning
confidence: 99%
“…The particular reactivity ratio of comonomers is the essential factor in regulating the sequence structure of monomer units during chain growth polymerization. For general polymerization systems ( r 1 × r 2 > 0), sequence regulation of monomer units cannot be realized, and only block or statistical (random and gradient) sequence distributions can be prepared. , Recently, Kamigaito et al proposed a strategy to obtain sequence-defined vinyl polymers containing two double bonds in the main chain via ROMP of template ring monomers, and the polymer subsequently treated by hydrogenation resulted in methylene/styrene/acrylate/styrene/ethylene (i.e., SASEM) as the repeating units in the hydrogenation product . ROMP of 4-phenylcyclopentene (4PCP) has also been investigated, and quantitative homogeneous hydrogenation of P4PCP results in a precision E/S copolymer with a C5 skeleton (i.e., SEM) .…”
Section: Resultsmentioning
confidence: 99%
“…When THF was used as the solvent for copolymerization on a mixture of a-NCA and b-NTA, using Boc-a-L-Lys NCA and Bn-b 3 -LCHG NTA as the model, we found no significant gradient separation in compositional profile of two amino acid subunits within the poly-a/b-peptide chain, though Boc-a-L-Lys NCA have a slightly higher reactivity than Bn-b 3 -LCHG NTA according to the kinetic plot of residual monomer (Figures 3A-3C) and instantaneous copolymer composition F a-NCA (Figures 3C and S19). (Gleede et al, 2019) This copolymerization proceeded close to ''ideal copolymerization'' (r a-NCA 3 r b-NTA = 0.93, r a-NCA 3 r b-NTA = 1 means ideal copolymerization) (Yasir et al, 2020), which in combination with the instantaneous copolymer composition F a-NCA revealed that the resulting poly-a/b-peptide was a random-like copolymer and the b-amino acid residue has a nearly even distribution along poly-a/b-peptide chain (Figure 3C) (Yasir et al, 2020). Poly-a/b-peptides have proven to be important mimics and modifications of nature polypeptides, such as host defense peptide (HDP), to effectively improve the stability upon enzymatic degradation and therapeutic potential (Konai et al, 2018;Schmitt et al, 2004Schmitt et al, , 2007.…”
Section: Accessmentioning
confidence: 99%
“…Sulfonylaziridines are intriguing as monomers as they are able to polymerize under less stringent conditions than are typically associated with anionic polymerizations. In 2018, Wurm reported that the anionic ring-opening polymerization of methylsulfonylaziridines proceeds in wet DMF . The presence of water in the AROP of sulfonylaziridine is possible because the p K a of the sulfonylamides is comparable to that of water, and hydroxide is a poor nucleophile for sulfonylaziridine-ring opening.…”
Section: Introductionmentioning
confidence: 99%